2022
DOI: 10.3390/ncrna8020023
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Epitranscriptomic Marks Affecting lncRNA Structures and Functions

Abstract: Long non-coding RNAs (lncRNAs) belong to a class of non-protein-coding RNAs with their lengths longer than 200 nucleotides. Most of the mammalian genome is transcribed as RNA, yet only a small percent of the transcribed RNA corresponds to exons of protein-coding genes. Thus, the number of lncRNAs is predicted to be several times higher than that of protein-coding genes. Because of sheer number of lncRNAs, it is often difficult to elucidate the functions of all lncRNAs, especially those arising from their relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 142 publications
1
7
0
Order By: Relevance
“…This study and others clearly link the importance of lncRNAs in pathogenesis of T2D. Furthermore, lncRNAs can be the determinants to understand how RNA metabolisms are regulated through RNA modifications (epitranscriptomics), as we recently reviewed [92].…”
Section: Diabetes-associated Lncrnassupporting
confidence: 57%
“…This study and others clearly link the importance of lncRNAs in pathogenesis of T2D. Furthermore, lncRNAs can be the determinants to understand how RNA metabolisms are regulated through RNA modifications (epitranscriptomics), as we recently reviewed [92].…”
Section: Diabetes-associated Lncrnassupporting
confidence: 57%
“…In recent years, there has been increasing interest in noncoding RNAs-mediated epigenetic regulation of transcription in diverse biological functions [ 29 , 30 ]. The function of miRNAs in Achilles tendinopathy has been investigated, but the role of lncRNAs remains largely obscure.…”
Section: Discussionmentioning
confidence: 99%
“…55 LncRNAs may increase or decrease gene expression during transcription by forming structures, such as the R loop, and after transcription. 56,57 LncRNAs can act as precursors for miRNAs or bind to these regulatory molecules as Competing Endogenous RNA (ceRNA) and disrupt their inhibitory function on target genes. 58,59 Also, LncRNAs play a crucial role in several cellular processes, including cell growth, apoptosis, and tumorigenesis.…”
Section: Lncrnas and Mechanisms Of Actionmentioning
confidence: 99%
“…Initially, lncRNAs were also considered to be evolutionary byproducts or transcriptional noise 54 ; however, it has been shown that lncRNAs have various functions and are involved in processes such as chromatin remodeling, mediating enzyme activity, transcriptional editing, and regulation 55 . LncRNAs may increase or decrease gene expression during transcription by forming structures, such as the R loop, and after transcription 56,57 . LncRNAs can act as precursors for miRNAs or bind to these regulatory molecules as Competing Endogenous RNA (ceRNA) and disrupt their inhibitory function on target genes 58,59 .…”
Section: Lncrnas and Mechanisms Of Actionmentioning
confidence: 99%